Tetrabutylphosphonium Bromide Reduces Size and Polydispersity Index of Tat2:siRNA Nano-Complexes for Triticale RNAi - Pepper, Jordan T.; Maheshwari, Priti; Ziemienowicz, Alicja; Hazendonk, Paul; Kovalchuk, Igor; Eudes, François (Frontiers in Molecular Biosciences, 2017)
Cell-penetrating peptides (CPPs) are short 8-30 amino-acid oligopeptides that act as effective transducers of macromolecular cargo, particularly nucleic acids. They have been implemented in delivering dsDNA, ssDNA and dsRNA into animal and plant cells. CPPs and nucleic acids form nano-complexes that are often 100-300 nm in size but still effectively transit the cell membrane of animal cells, but are less effective with plant cells due to the plant cell wall. To overcome this obstacle, nano-complexes of the CPP Tat2 and various lengths of nucleic acid (21-mer siRNA duplex (dsRNA) to 5.5 kb circular plasmid) were evaluated for size using dynamic light scattering (DLS), under conditions of increasing ionic strength (Ic) and addition of phase transfer catalyst salts (tetrabutylammonium bromide-TBAB and tetrabutylphosphonium bromide-TBPB) and sugars (maltose-mannitol solution). It was found that the combination of 21-mer siRNA:Tat2 complexes with TBPB produced small 10-20 nm diameter nano-complexes with a polydispersity index (PDI) of 0.1. Furthermore, it was found that for each length of nucleic acid that a linear mathematical relationship existed between the theoretical volume of the nano-complex and the nucleic acid length. Next, nano-complex formulation was tested for its ability to carry small interfering RNA molecules into plant cells and to trigger silencing of phytoene desaturase (PDS) in Triticale leaves. RT-qPCR showed 75% suppression of PDS, demonstrating that TBPB acts as an adjuvant in effecting the entry and efficacy of siRNA in young Triticale plants.